2020
DOI: 10.3389/fendo.2020.558593
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory, and Treatment Profiles of Silent Corticotroph Adenomas That Have Transformed to the Functional Type: A Case Series With a Literature Review

Abstract: Purpose: Silent corticotroph adenoma (SCA) is clinically non-functional pituitary adenoma with expression of corticotropin or Tpit. To further understand the characteristics of this rare type of SCA transforming to a functional SCA, we retrospectively reviewed SCAs that converted to typical Cushing's syndrome at a tertiary medical center and the relevant literature. Methods: Patients were identified based on the diagnosis of pituitary adenoma without symptoms of hypercortisolism at the initial visit with posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Little by little, ACTH could gradually and eventually rise to a higher level to cause clinical manifestations of Cushing’s syndrome. Indeed, the transformation took a median of 30 months, with the longest interval being 10 years summarized by Zheng et al [ 40 ]. Additionally, a most recent mechanism proposed by Araki et al [ 28 ] suggested that the sequential hypomethylation of the second promoter might activate POMC and promote ACTH secretion in the phenotypic transition.…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…Little by little, ACTH could gradually and eventually rise to a higher level to cause clinical manifestations of Cushing’s syndrome. Indeed, the transformation took a median of 30 months, with the longest interval being 10 years summarized by Zheng et al [ 40 ]. Additionally, a most recent mechanism proposed by Araki et al [ 28 ] suggested that the sequential hypomethylation of the second promoter might activate POMC and promote ACTH secretion in the phenotypic transition.…”
Section: Pathogenesismentioning
confidence: 99%
“…Several studies have demonstrated that SCAs may transform into CD [ 11 , 40 ], which usually occur in the later course of SCAs [ 11 ]. Although the number of cases with transformation is very small, it necessitates attention because it indicates malignant tumor behavior [ 78 ].…”
Section: Postoperative Coursementioning
confidence: 99%
See 3 more Smart Citations